2022
DOI: 10.1177/13694332221113044
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of RC-ECC composite frame by eliminating shear reinforcement in beam-column joint: Shake table tests

Abstract: The inherent vulnerability of beam-column joints to seismic loading and steel congestion are two major research problems connected with beam-column joints of moment-resisting frames. The experimental study presented herein addresses these research questions and seeks to solve them by using Polyvinyl Alcohol based Engineered Cementitious Composite (PVA-ECC) in beam-column joints without transverse shear reinforcement. The study included the manufacture and shake table testing of two 1:3 reduced scale one bay tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Cai et al [33] investigated the ductility, stiffness, and energy dissipation of ECC/RC composite frames compared to RC frames, noting significant improvements in the ECC/RC frames. Khan et al [34,35] demonstrated that ECC beam-column joints without shear reinforcement still surpassed the code-specified shear resistance. Ye et al [36] and Yang et al [37] conducted low cyclic loading experiments on RECC-coupled shear walls, finding that using ECC materials in cast in situ connection areas significantly improved the seismic energy dissipation capacity compared to specimens without ECC.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [33] investigated the ductility, stiffness, and energy dissipation of ECC/RC composite frames compared to RC frames, noting significant improvements in the ECC/RC frames. Khan et al [34,35] demonstrated that ECC beam-column joints without shear reinforcement still surpassed the code-specified shear resistance. Ye et al [36] and Yang et al [37] conducted low cyclic loading experiments on RECC-coupled shear walls, finding that using ECC materials in cast in situ connection areas significantly improved the seismic energy dissipation capacity compared to specimens without ECC.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the relatively small lateral stiffness, damage often occurs after strong earthquake actions (Civil et al, 2008; Gong et al, 2013; Kamogawa et al, 2005). For those post-earthquake damaged structures, it would be too costly to totally rebuild, while the option of strengthening and repairing can improve the seismic performance of the structure with a smaller increase in investment (Khan et al, 2022; Prota et al, 2004; Yuan and Hu, 2021). Therefore, the importance of post-earthquake strengthening research has been attracted much attention (Fischer and Li, 2003; Mosallam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the RC frame, the ductility, stiffness and energy dissipation capacity of the ECC/RC composite frame are significantly improved. Through the shaking table test of ECC/RC composite frames, Khan et al [34,35] found that ECC beam-column joints without shear reinforcement still have better shear resistance than the codespecified value. Ye et al [36] conducted a low cyclic loading experiment on RECC-coupled shear walls.…”
Section: Introductionmentioning
confidence: 99%